HER3 expression in primary colorectal cancer including corresponding metastases in lymph node and liver. (April 2015) - Lédel, Frida; Stenstedt, Kristina; Hallström, Marja; Ragnhammar, Peter; Edler, David
Abstract Background. The human epidermal growth factor receptor complex (EGFR-1, HER2, HER3 and HER4) plays an important role in pathogenesis of solid tumours. We have previously reported high expression of HER3 in 70% of primary colorectal cancer (CRC) and that high expression were linked to a worse clinical outcome. The purpose of this study is to evaluate the HER3 expression in primary CRC and metastases. Material and methods. Tissue samples from primary CRC, corresponding lymph node metastases and liver metastases from 107 patients were analysed by immunohistochemistry. Results. Of 107 patients, 80% showed high HER3 expression in primary CRC tumours and 81% of the stage III patients presented high expression in the lymph node metastases. All patients had liver metastases and 82% presented high HER3 expression. HER3 expression in primary tumour correlated with expression in the corresponding lymph node metastases (r = 0.65, p < 0.001) and in the liver metastases (r = 0.45, p < 0.001). A correlation between HER3 expression in corresponding lymph node and liver metastases (r = 0.65, p < 0.001) was seen. Conclusion. High HER3 expression is seen in about 80% of primary CRC, corresponding lymph node metastases and liver metastases. There is a correlation between HER3 expression in primary tumour and metastases in CRC.